Study on extraction kinetics and formulation of natural mosquito repellent solution from marigold flower extracts - Noor Asikin, Ahmad Safri (2012)
The uses of plant extract which is Marigold flower can reduce the uses of chemical in mosquito repellent.Thus a research will be conduct to study on extraction kinetics and formulation of natural mosquito repellent solution using ultrasonic extraction from Marigold flower.During the extraction process,the reaction kinetics is study. Lutein has been extracted from Marigold using ultrasonic extraction at various extraction conditions such as different temperature, extraction time and volume of solvent due to its pharmacological actions.Lutein content in the extract is also determined by high performance liquid chromatography (HPLC) method.Based on experimental results,the content of lutein extracted from Marigold flower was found to be 2.5354% and the maximum amount of lutein extracted was obtained at temperature 45oC,volume of solvent at 150 ml and extraction time at 30 mins.The optimization results demonstrated that temperature was the influential variable on the extraction content of lutein.The extraction rate constant,k of lutein decreased with increasing temperature and volume of solvent,and the k values were (0.0405-0.2712) min-1.The lutein with higher concentration is used as main ingredient in mosquito repellent which gives the positive effect.